Neurological and psychiatric comorbidities of migraine: Concepts and future perspectives - Pelzer, Nadine; de Boer, Irene; van den Maagdenberg, Arn M.J.M.; Terwindt, Gisela M. (Cephalalgia, 2023)
Background This narrative review aims to discuss several common neurological and psychiatric disorders that show comorbidity with migraine. Not only can we gain pathophysiological insights by studying these disorders, comorbidities also have important implications for treating migraine patients in clinical practice. Methods A literature search on PubMed and Embase was conducted with the keywords “comorbidity”, “migraine disorders”, “migraine with aura”, “migraine without aura”, “depression”, “depressive disorders”, “epilepsy”, “stroke”, “patent foramen ovale”, “sleep wake disorders”, “restless legs syndrome”, “genetics”, “therapeutics”. Results Several common neurological and psychiatric disorders show comorbidity with migraine. Major depression and migraine show bidirectional causality and have shared genetic factors. Dysregulation of both hypothalamic and thalamic pathways have been implicated as a possibly cause. The increased risk of ischaemic stroke in migraine likely involves spreading depolarizations. Epilepsy is not only bidirectionally related to migraine, but is also co-occurring in monogenic migraine syndromes. Neuronal hyperexcitability is an important overlapping mechanism between these conditions. Hypothalamic dysfunction is suggested as the underlying mechanism for comorbidity between sleep disorders and migraine and might explain altered circadian timing in migraine. Conclusion These comorbid conditions in migraine with distinct pathophysiological mechanisms have important implications for best treatment choices and may provide clues for future approaches.